Islamic Religious Education Learning For Early Childhood in the Covid-19 Period - Ida Windi Wahyuni; Abdul Madjid (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2022)
Islamic religious education is given from the time the child is in the womb to birth. The pandemic period is the biggest challenge for families, where more children have to stay at home, limit going out of the house, and study at non-formal institutions. The purpose of this study was to determine the learning of Islamic religious education for early childhood during the pandemic in Riau Province. This research is expected to be an evaluation for parents and teachers in developing, providing examples and being role models for early childhood at home in everyday life during the pandemic. The number of subjects in this study amounted to 10 parents who came from several 4 districts in Riau Province. The results showed that Islamic religious education for early childhood has been implemented well, where parents and people around them always provide examples of good religious practices so that children are easier to imitate and implement every day. Parents' biggest hope is that this pandemic will end soon so that children can go back to school so that children's social development will develop better as a provision for their future